2016
DOI: 10.1016/j.chembiol.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-synthetic Oligosaccharide Conjugate Vaccine Candidate Confers Protection against Streptococcus pneumoniae Serotype 3 Infection

Abstract: The identification of immunogenic glycotopes that render glycoconjugate vaccines protective is key to improving vaccine efficacy. Synthetic oligosaccharides are an attractive alternative to the heterogeneous preparations of purified polysaccharides that most marketed glycoconjugate vaccines are based on. To investigate the potency of semi- synthetic glycoconjugates, we chose the least efficient serotype in the current pneumococcal conjugate vaccine Prevnar 13™, Streptococcus pneumoniae serotype 3 (ST3). Glycan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 59 publications
3
56
0
1
Order By: Relevance
“…1A). Octasaccharides derived from ST8 CPS hydrolysis have been found to induce protective immunity (16), but based on the findings that glycans as small as di- to tetrasaccharides induced protective immunity against other S. pneumoniae serotypes (8, 9, 17), we reasoned that a collection of all four tetrasaccharide frameshifts would cover most glycotopes in ST8 CPS that are relevant for antibody reverse engineering. We used automated glycan assembly (AGA) to synthesize conjugation-ready variants of all four frameshifts A( 1 ), B( 2 ), C( 3 ) and D( 4 ) from polystyrene resin 5 and orthogonally protected building blocks 6–11 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). Octasaccharides derived from ST8 CPS hydrolysis have been found to induce protective immunity (16), but based on the findings that glycans as small as di- to tetrasaccharides induced protective immunity against other S. pneumoniae serotypes (8, 9, 17), we reasoned that a collection of all four tetrasaccharide frameshifts would cover most glycotopes in ST8 CPS that are relevant for antibody reverse engineering. We used automated glycan assembly (AGA) to synthesize conjugation-ready variants of all four frameshifts A( 1 ), B( 2 ), C( 3 ) and D( 4 ) from polystyrene resin 5 and orthogonally protected building blocks 6–11 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3B) and monitored the immune response by glycan microarray. We included disaccharide 13 and tetrasaccharide 14 , a synthetic dimer of cellobiuronic acid that is an ST3 vaccine candidate (6, 17), in the microarray experiment to evaluate the glycan binding characteristics of immune sera (Fig. 3C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ST3 CPS is a linear polysaccharide that is composed of a repeating disaccharide made of β‐linked d ‐glucuronic acid (GlcA) and d ‐glucose (Glc), specifically, →3)‐β‐ d ‐GlcA‐(1→4)‐β‐ d ‐Glc‐(1→. Several short oligosaccharide fragments of ST3 CPS and their protein conjugates have been synthesized and immunologically evaluated . It was disclosed that these semisynthetic conjugate vaccines could elicit robust ST3 CPS‐specific IgG antibodies, whose titers increased with the ST3 oligosaccharide chain length .…”
Section: Introductionmentioning
confidence: 99%
“…It was disclosed that these semisynthetic conjugate vaccines could elicit robust ST3 CPS‐specific IgG antibodies, whose titers increased with the ST3 oligosaccharide chain length . Furthermore, glycan array screening revealed that an ST3 tetrasaccharide could be well‐recognized by ST3‐specific protective human monoclonal antibodies, and opsonophagocytosis assays showed that a CRM 197 protein conjugate of the tetrasaccharide could induce immunoprotection . In general, it was also revealed that ST3 CPS oligosaccharide–protein conjugates could form effective vaccines to protect mice from intraperitoneal challenge with lethal doses of ST3 .…”
Section: Introductionmentioning
confidence: 99%